Abnormal Glucose Metabolism and Insulin Resistance Are Induced via the IRE1α/XBP-1 Pathway in Subclinical Hypothyroidism - Xu, Chao; Zhou, Lingyan; Wu, Kunpeng; Li, Yujie; Xu, Jin; Jiang, Dongqing; Gao, Ling (Frontiers in Endocrinology, 2019)
Subclinical hypothyroidism (SCH) and diabetes mellitus are closely related and often cluster in individuals. However, this connection is still uncertain, as well as the underlying mechanism. In this study, we firstly re-analyzed the data of a mature database (NHANES, 1999 2002) and found that both fasting plasma glucose levels and the proportion of hyperglycemic subjects in SCH patients were higher than those in euthyroid controls. And SCH was associated with a 2.29-time increased risk for diabetes. Then, we established an SCH mouse model and applied OGTT and ITT. SCH mice exhibited impaired glucose and insulin tolerance. Increased HOMA-IR index and decreased ISI index, indicating insulin resistance (IR), were also observed in the SCH state. Hepatic ERp29 and Bip, as well as IRE1α and XBP-1s induced significantly in SCH mice, suggesting the activation of endoplasmic reticulum (ER) stress, especially the IRE1α/XBP-1s pathway. Interestingly, when we rectified ER stress by using 4-phenyl butyric acid, abnormal glucose metabolism and IR status in SCH mice apparently improved. Our findings suggested that ER stress, predominately the IRE1α/XBP-1s pathway, may play a pivotal role in abnormal glucose metabolism and IR induced by SCH, which may provide potential strategies for the prevention and treatment of diabetes.